Bosnians against the Ottoman Empire – rebellion of the Muslim population in Bosnia in the first half of the 19th century - Lis, Tomasz Jacek (Balcanica Posnaniensia. Acta et studia, 2021)
This paper presents the history of anti-Ottoman rebellions, which occurred in Bosnia in the first half of the 19th century. The main initiators of these uprisings were not Christians, as it happened in Serbia, but local Muslim citizens, who were not accepting Stambuls’ agenda towards European parts of the Ottoman Empire. In the paper I would like to investigate some of the most important events in the history of Bosnia: Husejn kapetan Gradaščević rebellion; social turmoil of `30s and `40s, and the final confrontation of Herzcegovinian vezir Rizvanbegović with an army of Omer pasha Latas, who received orders to pacify riots in Bosnia and Herzegovina. The paper is based on the scientific literature, public archive documents and narratives sources – memoirs and travel diaries.